Kemampuan Fertilisasi Spermatozoa Sexing dan Perkembangan Awal Embrio Secara In Vitro pada Sapi - Alvien Nur Aini; Mohamad Agus Setiadi; Ni Wayan Kurniani Karja (Jurnal Sain Veteriner, 2016)
The aim of the present study was to investigate the fertilization ability of bovine oocytes and early bovine embryonic development in vitro, fertilized by frozen X and Y sperm separated by bovine serum albumin (BSA) gradient column. Oocytes were collected from slaughter house ovarian by flushing and slicing technique. Oocytes were than maturated in tissue culture medium (TCM) 199 supplemented with 10 IU/ml pregnant mare’s serum gonadotropin (PMSG), 10 IU/ml human chorionic gonadotropin (hCG) and 10% fetal bovine serum (FBS) for 24 h in 5% CO2 incubator 39oC. Oocytes then fertilized with three kind of different frozen spermatozoa (X,Y and unsexing spermatozoa as control) for 14 h with final concentration 2x106 spermatozoa/mL. Embryos were cultured insynthetic oviductal fluid (SOF) supplemented with essential and non essential amino acid and 0.3% bovine serum albumin (BSA) for 96 h. Results of the experiments revealed that there was no significant difference (P>0.05) in thefertilization ability (49.17%; 51.40%; 53.42%) for X, Y and control group, respectively. No significant difference (P>0.05) in the number of embryos development (47.77%; 48.25%; 54.43%) for X, Y and control group, respectively. Furthermore, only small number of embryos could pass development blockade (23.80%; 26.08%; 23.61%) for X, Y and control spermatozoa with statistically no significant difference (P>0.05). It is concluded that sexed spermatozoa separated by BSA gradient column had comparable fertilization ability with unsexing spermatozoa and had ability to supported early embryonic development.